El ingreso mínimo garantizado en la Unión Europea Entre la crisis económica y el Pilar Europeo de los Derechos Sociales: aspectos críticos de un instrumento legal positivo y esencial para combatir la pobreza - Nato, Alessandro (2019)
Guaranteed minimum income is one of the most important rights of citizens of the Member States of the European Union. It is both an instance of market efficiency and those of inclusion and solidarity. The models of guaranteed minimum income have different characteristics between Member States (national welfare, access criteria, amount and duration of the transfer, methods of administration and place in the framework of social policies). Recently, EU has taken initiatives to sensitize the Member States on the strengthening of minimum income to help European citizens better. European institution have emphasized (in acts of soft-law) that guaranteed minimum income is an institution that allows the full and free participation of the individual in the social and productive reality of the community to which he belongs. However, in a context of economic crisis and the increase of vulnerable social groups, the minimum income has lost its efficacy and efficiency. Because of this situation, social inclusion measures need to be reinforced in order to assure a guaranteed minimum income to EU citizens, who do not have the financial resources to ensure a decent life. This article examines these issues. On the one hand, it outlines the ongoing dynamics in the EU level and examines the EU system against poverty and social exclusion. In addition, it studies the recent proposals under discussion such as the contribution of the European Pillar of Social Rights. On the other hand, it deepens the knowledge on the critical elements of the minimum income schemes in the Member States.